EXPERT-BASED FORECASTING FOR MALAYSIAN PROPERTY MARKETS - Razali, Muhammad Najib (Journal of Technology Management and Business, 2015)
This research attempt to develop a property forecasting procedure for the various Malaysian property markets to enable more informed decision-making by using local property experts’ opinion. Data were collected from two sources using two methods: interviewing property players and conducting participant observation about self-directed learning of property players in the property investment practice. Unlike other research that heavily rely on the econometrics model to forecast the property markets, this research based on the perception which is also major contribution to the property market growth. The findings from this research provide a detailed depiction of the many facets of property forecasting, revealing in particular the nature and extent of the critical role performed by human judgement. This research study on the Malaysian property markets comprises office and retail space demand.